Teori Tipologi Karier John Holland: Suatu Kajian Literatur dalam Konseling Karier - Meylani, Ade Siska; Zulaikha, Fatin; Aulia, Nesa; Pala, Ropelta; Naila Safitri, Umniyyah; Subhan, Mhd (Jurnal Bimbingan dan Konseling Pandohop, 2026)
This study examines John Holland’s Career Typology Theory within the context of career counseling through a literature review approach. Holland’s theory posits that individuals’ career choices reflect their personality characteristics and that career satisfaction and success are more likely to be achieved when there is congruence (person–environment fit) between individuals and their work environments. The typological model classifies personality into six primary types known as RIASEC: Realistic, Investigative, Artistic, Social, Enterprising, and Conventional. Relevant national and international scholarly sources were systematically reviewed to analyze the conceptual development, application, and contemporary relevance of Holland’s theory in career counseling practice. The findings indicate that Holland’s typology remains highly relevant in supporting individuals’ understanding of their interests, abilities, and personality tendencies, as well as in facilitating structured and rational career exploration and decision-making. Furthermore, the theory has provided a foundational framework for the development of widely used career assessment instruments. Nevertheless, the literature underscores the need to adapt and integrate Holland’s theory with contemporary career approaches to address the increasingly complex and dynamic nature of the digitalized world of work. This article contributes theoretically and practically by offering insights for career counselors and educators on applying Holland’s theory in a more contextual and sustainable manner in modern career counseling.